Comprehension, mapping and reporting of climate-related risks among listed firms in Sweden - Fredrik N. G. Andersson; Susanne Arvidsson (Lund University, School of Economics and Management, Lund Institute for Sustainability Impact, 2021)
We study the comprehension, mapping, and reporting of climate-related risks among firms listed on the NasdaqOMX stock exchange in Stockholm. Our study contains two parts: i) a study on the firms' external communication through their annual reports, sustainability reports and webpages, and ii) a follow-up survey addressed to each firm's management team. We find that firms are likely to engage in some form of mapping and reporting of climate-related risks. However, their comprehension of the nature of these risks, underlying problems, and what a climate transition implies varies across firms and industries. There are also substantial variations in the method employed to map and report climaterelated risks. Our results further suggest that firms use the Task Force on Climate-related Financial Disclosures' recommendations (TCFD) on how to map and report climate risks as a learning tool to improve their climate-risk management. However, as a voluntary initiative it is insufficient to generate substantial change. Consequently, policymakers should focus on improving firms' comprehension of what constitutes a climate-risk, how to map such risks and how to report them. The mapping and reporting of climate-related risk may otherwise prove an inefficient tool to redirect and accelerate investments promoting a low-carbon and climate-resilient economy.
Keywords: M40; Q54; Q56; Q58; 330; climate policy; climate change; climate-risk management; climate-related risks; nonfinancial reporting; TCFD; NFRD